2002
DOI: 10.1038/modpathol.3880556
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of FISH, RT-PCR, PCR, and Immunohistochemistry for the Diagnosis of Mantle Cell Lymphomas

Abstract: Mantle cell lymphoma (MCL) diagnosis first relies on morphology and phenotype that may overlap with other B-cell lymphomas. Therefore, the demonstration of t(11;14)(q13;q32), the cytogenetic hallmark of MCL, is considered of diagnostic value. By studying a series of 35 MCL with characteristic morphology and phenotype (CD5؉, CD10؊, CD20؉, CD23؊), we have evaluated the applicability and the sensitivity of interphase fluorescence in situ hybridization (FISH) for t(11;14) detection and other techniques: (1) polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 41 publications
5
79
1
1
Order By: Relevance
“…Utilizing the IGH/CCND1 probes, Li et al identified positive results in 51 MCL cases studied but not in any of the 12 control cases [9]. Belaud-Rotureau et al demonstrated CCND1 by FISH in 34 of 35 MCL cases [12]. Our study confirms the results of the previous studies in terms of sensitivity and specificity of FISH for the diagnosis of MCL.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Utilizing the IGH/CCND1 probes, Li et al identified positive results in 51 MCL cases studied but not in any of the 12 control cases [9]. Belaud-Rotureau et al demonstrated CCND1 by FISH in 34 of 35 MCL cases [12]. Our study confirms the results of the previous studies in terms of sensitivity and specificity of FISH for the diagnosis of MCL.…”
Section: Discussionsupporting
confidence: 87%
“…Cytogenetics, Southern blotting, and PCR have been used for this purpose. The sensitivity of cytogenetics and Southern blotting ranges from 37% to 80% [7,9,12]. The PCR has an even lower sensitivity in the range of 50-60% because of the large number of 11q13 breakpoints scattering over a region of more than 120 kb [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-color FISH analysis was performed using an IGH-CCND1 probe set (Vysis Inc., Downer's Grove, IL), as described elsewhere. 20,21 FC FNC specimens were processed within 2 hours, and the cell suspensions were washed twice by centrifugation for 5 minutes at 2500 revolutions per minute, removing the supernatant fluid and adding 400 L of PBS. The final suspension was divided into four or more tubes when sufficient cells were available.…”
Section: Patients and Fncmentioning
confidence: 99%
“…6). 19,21 The phenotype CD3ϩ, CD56ϩ, CD19Ϫ, CD10Ϫ/CD23Ϫ was specific for natural killer cell lymphoma. 22,25 In large cell and anaplastic NHL, the phenotype CD19ϩ, CD19/CD5Ϫ, CD19/CD10Ϫ, CD19/CD23Ϫ, CD38/ CD56Ϫ was observed the most frequently.…”
Section: Patients and Fncmentioning
confidence: 99%